(untitled) (Bangladesh Journal of Microbiology, 2019)
Current study attempted to check out the microbiological quality of some common sterile ointment commonly implemented for the treatment of eye infections in Bangladesh. Seventeen (17) different eye ointment (T-Mycin, Aprocin, Bactin, Optimox and Cloram, Hypomer gel, Sonexa, Polytracin, Cero, Aristobet, Lotepred, Herpigel, Gentob, Xoviral, Zirgan, Xovir, Tomycin, Tobirax, AFm-plus and Parafresh) were microbiologically examined through common and traditional cultural methods. Total viable bacterial and fungal contamination was found up to 106 and 105 cfu/ml respectively. Among the 17 samples T-Mycin, Aprocin, Sonexa, Polytracinand Tomycinwere free from fungal contamination. All the samples significantly exceeded United States Pharmacopeia (USP) or British Pharmacopeia (BP) limit (<102 cfu/ml) in case of Total viable bacteria and fungus contamination. While the coliforms (Escherichia coli and Klebsheilla spp.) were absent in all samples, the prevalence of Staphylococcus spp. was 100% in all samples up to 103 while the Bacillus spp. was found up to 102 cfu/ml. Pseudomonas spp. was cultivated in TMycin, Aprocin Hypomer gel, Sonexa, Polytracin, Cero, Aristobet and Lotepred up to 103cfu/ml. All the 5 drugs showed their antibacterial potency with satisfactory range of zone diameter againstE. coli, Pseudomonas spp., Staphylococcus spp., Klebsheilla spp. and Bacillus spp. In case of all 17 ointments the average zone diameter range was noticed within 13mm-22mm. The highest zone diameter (22mm) was recorded against E. coli produced by Aprocin and minimum zone diameter (13mm) was recorded against Bacillus spp. produced by Bactin, Optimox and Cloram.Gentamicin and Streptomycin were used as positive control against the tested bacteria. Bangladesh J Microbiol, Volume 35 Number 2 December 2018, pp 122-126